Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1080/00103620601093579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity and Some Chemical Properties of the Under- and Intercanopy Soils on Range Plants in a Dry Region of Southern Iran

Abstract: The present study was conducted in a dry region in southern Iran to evaluate the effects of different Atriplex species on the salinity, soluble ions, and some of the other chemical properties of under-and intercanopy soils. The research region was divided into five separate sites with vegetation cover of the range plants Atriplex lentiformis, A. nummularia, and A. halimus (all newly introduced species) and A. leucoclada and Salsola rigida (both native species). Four 1-kg soil samples (from under-and interspace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
6
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 48 publications
6
6
3
Order By: Relevance
“…The observed 81% increase in EC is rather similar in magnitude to the 125% and 178% changes measured by Sharma & Tongway () in the 0–7·5 cm layer of two different plantations and to the 148% reported by Sameni & Soleimani () for the 0–10 cm layer. No significant EC increase was instead observed by Zucca et al .…”
Section: Discussionsupporting
confidence: 88%
“…The observed 81% increase in EC is rather similar in magnitude to the 125% and 178% changes measured by Sharma & Tongway () in the 0–7·5 cm layer of two different plantations and to the 148% reported by Sameni & Soleimani () for the 0–10 cm layer. No significant EC increase was instead observed by Zucca et al .…”
Section: Discussionsupporting
confidence: 88%
“…It is clear that these nutrients followed the distribution pattern of the soil OM in the two locations, those under canopy sites were well pronounced. Similar observations have been reported for different plant species in arid and semiarid regions (Tiedemann and Klemmedson, 1973ab;Bernhard-Reversat, 1996;Virginia & Jarrell, 1983;Karimian & Ramzi, 1990;Mazzarino et al, 1991;Sameni & Soleimani, 2006). Callardo (2003) stated that elements such as N, which cycle mainly through biological processes, show different spatial distribution compared to elements such as P, which cycle through both biological and geological processes.…”
Section: Resultssupporting
confidence: 61%
“…For all species, the value of OM content was higher in the soil beneath canopies as compared to the interspace soil (Table 2). Higher OM contents of the soil under canopies of different Atriplex species in comparison with the interspace soil have been reported by Sameni and Soleimani (2007). Khanmirzaei et al (2009) observed that the content of OM beneath Eucalyptus trees was higher than between them.…”
Section: Soil Characteristicsmentioning
confidence: 67%
“…Sameni and Soleimani (2007) observed that increases in EC values beneath Atriplex species were in association with a decrease in pH values. The availability of Fe is low in high-pH soils (Ghasemi-Fasaei et al 2005), and lower pH values in soil under canopy can enhance the availability of this element.…”
Section: Soil Characteristicsmentioning
confidence: 88%
See 1 more Smart Citation